Cerebral Venous Thrombosis, A Retrospective Study of 14 Patients and Review of Literature - Çağatay Öncel; L.sinan Bir; Göksemin Acar; Attila Oğuzhanoğlu; Türker Şahiner; Filiz Tokgöz; Yılmaz Kıroğlu (Türk Nöroloji Dergisi, 2008)
OBJECTIVE: Cerebral venous thrombosis is thrombosis of brain veins and sinuses which are due to prothrombotic process. They present with various neurological symptoms. The annual incidence is 3- 4/million. METHODS: Symptoms, demographic data, etiologic factors, clinical and radiological features of 14 consecutive patients between July 1st 2006 and July 1st 2008 with cerebral venous thrombosis are evaluated retrospectively. RESULTS: The study group comprised 4 men and 10 women. Their mean age was 44.2±19 years. Headache is the most frequent symptom, present in %92.8 of the patients. Papilloedema (50%), impairment of level of consciousness (14.3%), vertigo (14.3%), visual disturbances (14.3%) were the other symptoms. Eight patients were admitted just because of headache. Seven patients had one and seven patients had more than one sinus involvement. CONCLUSION: The incidence is rare but the outcome of this disorder is generally favourable if diagnosed. Cerebral venous thrombosis must be remembered in the differantial diagnosis of headaches of unknown etiologie